2014
DOI: 10.1063/1.4885342
|View full text |Cite
|
Sign up to set email alerts
|

The effect of turbulent kinetic energy on inferred ion temperature from neutron spectra

Abstract: Measuring the width of the energy spectrum of fusion-produced neutrons from deuterium (DD) or deuterium-tritium (DT) plasmas is a commonly used method for determining the ion temperature in inertial confinement fusion (ICF) implosions. In a plasma with a Maxwellian distribution of ion energies, the spread in neutron energy arises from the thermal spread in the center-of-mass velocities of reacting pairs of ions. Fluid velocities in ICF are of a similar magnitude as the center-of-mass velocities and can lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 27 publications
2
62
0
Order By: Relevance
“…Also shown are simulated ratios from 1D HYDRA simulations (black crosses) and predicted ratios in apparent T ion due to a nonthermal contribution from flows according to Ref. [23], assuming a thermal T ion = 0 keV (solid purple line), thermal T ion = 1.5 keV (dot-dashed line), and thermal T ion = 2 keV (double-dot-dashed line).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Also shown are simulated ratios from 1D HYDRA simulations (black crosses) and predicted ratios in apparent T ion due to a nonthermal contribution from flows according to Ref. [23], assuming a thermal T ion = 0 keV (solid purple line), thermal T ion = 1.5 keV (dot-dashed line), and thermal T ion = 2 keV (double-dot-dashed line).…”
mentioning
confidence: 99%
“…It should be noted that the strong coupling of deuterons and tritons will result in equality of the true ion temperatures. In a recent paper, Murphy [23] articulates that the quantity inferred from the neutron spectrum variance, which we will call apparent T ion , for a homogeneous nonstationary plasma is the sum of the thermal broadening and a macroscopic broadening from the line-of-sight-projected bulk fluid velocity variance σ…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the 3D simulations continue the trend of under predicting the hot spot ion temperatures and over predicting the implosion DSRs, although the 3D DSR results are clearly closer to agreement. This is notable in that the 3D simulations fully account for the current best prediction of the 3D hot spot flows that are hypothesized to account for the measured ion temperatures [38,39]. That is, the realistic stagnation process in the presence of hohlraum asymmetries and capsule perturbations is modeled fully in these simulations and yet continues to disagree with the measured hot spot ion temperature.…”
Section: D Simulationsmentioning
confidence: 83%
“…Recent theoretical work has suggested that bulk fluid motion of a TN plasma can have a noticeable broadening effect on neutron spectrum width in inertial confinement fusion, [42][43][44] potentially causing an erroneously high ion temperature to be inferred from the spectrum width. This effect was included in the simulations of the 15 MA gas puff and 2 MA DPF.…”
Section: B Thermonuclear Spectra Broadened By Bulk Fluid Motionmentioning
confidence: 99%